Left Ventricular Hypertrophy in Pediatric Hypertension: A Mini Review - Woroniecki, Robert P.; Kahnauth, Andrew; Panesar, Laurie E.; Supe-Markovina, Katarina (Frontiers in Pediatrics, 2017)
Adults with arterial hypertension (HTN) have stroke, myocardial infarction, end-stage renal disease (ESRD) or die at higher rates than those without. In children, HTN leads to target organ damage (TOD), which includes kidney, brain, eye, blood vessels and heart, which precedes “hard outcomes” observed in adults. Left ventricular hypertrophy (LVH), or an anatomic and pathologic increase in left ventricular mass (LVM) in response to the HTN is a pediatric surrogate marker for HTN induced morbidity and mortality in adults. This mini review discusses current definitions, clinically relevant methods of LVM measurements and normalization methods, its epidemiology, management and issue of reversibility in children with HTN. Pediatric definition of LVH and abnormal LVM is not uniformed. With multiple definitions, prevalence of pediatric HTN-induced LVH is difficult to ascertain. In addition while in adults cardiac magnetic resonance (CMR) imaging is considered “the gold standard” for LVM and LVH determination, pediatric data is limited to “special populations”; ESRD, transplant, obese children. We summarize available data on pediatric LVH treatment and reversibility, and offer future directions in addressing LVH in children with HTN.